2012
DOI: 10.1583/11-3692.1
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Stenting vs. Extrathoracic Surgical Bypass for Symptomatic Subclavian Steal Syndrome

Abstract: Both endovascular stenting and extrathoracic surgical bypass are safe and effective treatments for subclavian steal syndrome in the short and medium term; however, extrathoracic surgical bypasses are more durable in the long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 27 publications
0
60
0
Order By: Relevance
“…While several case reports and case series describe experiences using one particular technique, only six studies to date have compared the results of a percutaneous endovascular technique to surgical subclavian artery revascularization [50][51][52][53][54][55]. These six studies were published between 1989 and 2012, and as a result compare various open surgical techniques (carotidsubclavian bypass, carotid-to-carotid bypass, subclavian-to-subclavian bypass, subclavian-to-axillary bypass, and subclavian carotid transposition) to different endovascular techniques (PTA alone, PTA with balloon-expandable stent, PTA with self-expanding stent) as technology advanced and for different indications prohibiting a meaningful meta-analysis.…”
Section: Percutaneous Endovascular Intervention Versus Surgical Revasmentioning
confidence: 99%
“…While several case reports and case series describe experiences using one particular technique, only six studies to date have compared the results of a percutaneous endovascular technique to surgical subclavian artery revascularization [50][51][52][53][54][55]. These six studies were published between 1989 and 2012, and as a result compare various open surgical techniques (carotidsubclavian bypass, carotid-to-carotid bypass, subclavian-to-subclavian bypass, subclavian-to-axillary bypass, and subclavian carotid transposition) to different endovascular techniques (PTA alone, PTA with balloon-expandable stent, PTA with self-expanding stent) as technology advanced and for different indications prohibiting a meaningful meta-analysis.…”
Section: Percutaneous Endovascular Intervention Versus Surgical Revasmentioning
confidence: 99%
“…8,[14][15][16][17][18][19][20] Balloon angioplasty and stenting can be performed when stenting is unlikely to compromise the vertebral circulation. Technical success of the percutaneous approach can be achieved in >90%, with 5-year patency rates of 85%.…”
Section: Managementmentioning
confidence: 99%
“…21,22 Although there are studies concluding that endovascular approach is as safe and efficacious as the open surgical treatment, even for high-grade lesions, 23,24 Farina et al 25 showed a statistically increased restenosis rate after PTA compared with surgery. In addition, AbuRahma et al 26 compared the results of PTA/stenting in the subclavian artery with the results of CSBP grafts.…”
Section: Discussionmentioning
confidence: 99%